(untitled) (Research, Society and Development, 2020)
The virtual world has been the preferred and recurring field of crimes, among the many crimes committed in the virtual environment, cyber-pedophilia stands out, that is, pedophilia practiced through the Internet, with children and adolescents as its main victims. In this way, the present work is about cyber-pedophilia, that is, sexual crimes against children and adolescents practiced through the internet. The review covered scientific articles, monographs, theses and dissertations published and available in the databases: CAPES (Coordinating Improvement of Higher-Level Personnel), SciELO (Scientific Electronic Library Online) and Google academic. Through the study, it can be seen that the Internet is the gateway to the spread of cyber-crime, it is necessary to address the difficulties within the reality, advances and potential accumulated around this strategy, contributing with data that aid in the management and strategies in the legal sphere, as well as, serve as the basis for new research.